Modification of Intrauterine Catheter Device to Manage Reocclusion Following Cervical Dysgenesis Surgery: A Case Series - Tyas Priyatini; Rodiani, Rodiani (Andalas Obstetrics And Gynecology Journal, 2025)
Background: Cervical dysgenesis is an extremely rare type of Mullerian anomalies causing obstructive symptoms. Conservative surgery of neocervix may be related to reocclusion of the genital tract and further increase the risk of reoperation. The presence of uterine malformation may also complicate this condition and lead to challenges for normal anatomy restoration. Case presentation: We present three cases of primary amenorrhea and obstructive symptoms caused by reocclusion following cervicovaginal conservative surgery. A neovagina was created using amniotic graft, followed by the insertion of intrauterine catheter device using a syringe barrel to maintain canalization and prevent reccurent occulsion. Double approach technique (laparotomy hysterotomy and transvaginal approach) was used in the two cases and one case underwent transvaginal surgery. Three months follow-up revealed normal menstruation and rather satisfying anatomical outcome. Clinical discussion: Treatments should aim to relieve obstructive symptoms, improve function, and preserve fertility. Conservative surgical approach to manage cervical dysgenesis warrants challenges in preventing reocclusion. Surgery mainly consists of creating neocervix, neovagina if needed, and maintaining the continuity of the genital tract. Conclusion: Intrauterine catheter device using a syringe barrel is a simple and feasible option with satisfactory anatomical as well as functional outcome to manage cervical dysgenesis